Future climate and agricultural farming systems affect the fungal plastisphere of different biodegradable plastics at the early stage of field degradation - Benjawan Tanunchai; Martin Schädler; Matthias Noll (Environmental Sciences Europe)
Abstract Background The use of biodegradable mulch films has an advantage over non-biodegradable ones, as it offers degradation by microbes under environmental conditions. Nevertheless, less is known about the microbial colonization of different biodegradable plastics under different agricultural systems and climate change conditions. In the current study, the plastic degradation experiment was conducted at the Global Change Experimental Facility platform, specifically in conventional and organic farming systems, both under ambient and future climatic conditions. In this study, we investigated the early fungal colonizers associated with polybutylene-succinate (PBS) and polybutylene adipate-co-terephthalate (PBAT) with polyethylene (PE) as a reference in comparison to the initial soil fungal community. Results We found a distinct pattern between soil and plastisphere fungi. Soil fungi were dominated by Sordariomycetes (mainly Gibellulopsis, Fusarium, and Gibberella), and fungi in plastics were dominated by Dothideomycetes (mainly Mycosphaerella, Alternaria, and Cladosporium). These microbes were previously reported as plastic colonizers and potential plastic degraders. We found that agricultural systems affect both fungal richness and community composition of the plastisphere. Plastic type significantly affected the fungal richness, but not the fungal community composition. The two different agricultural systems undergo different treatments, including crop rotation and fertilization, which in turn impact the fungal colonization of the biodegradable plastics. Conclusions This study provides new insights into factors that affect early fungal colonization of different biodegradable plastics under real field conditions using high-throughput sequencing. These data are of high relevance to evaluate the plastic composition for adjusted rate of plastic biodegradation for upcoming mulch film products.